2016
DOI: 10.1002/cbic.201600493
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Small‐Molecule PHD2 Zinc Finger Inhibitors that Activate Hypoxia Inducible Factor

Abstract: The Prolyl Hydroxylase Domain protein (PHD):Hypoxia Inducible Factor (HIF) pathway is the main pathway by which changes in oxygen concentration are transduced to changes in gene expression. In mammals, there are three PHD paralogues, and PHD2 has emerged as a particularly critical one for regulating HIF target genes such as ERYTHROPOIETIN (EPO), which controls red cell mass and hematocrit. PHD2 is distinctive among the three PHDs in that it contains an N-terminal MYND type zinc finger. We have proposed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The interaction with pVHL requires the hydroxylation of specific proline residues of AKT1 [21] (table 1). AKT1 hydroxylation is mediated by PHD2, which in turn is the main regulator of HIF-1α hydroxylation [23,[50][51][52]. The interaction promotes AKT1 functional inhibition, while, similarly to what was observed for PKCδ, it seems to have no effect on AKT1 degradation.…”
Section: Von Hippel-lindau Protein and The Regulation Of Kinases Activitymentioning
confidence: 70%
“…The interaction with pVHL requires the hydroxylation of specific proline residues of AKT1 [21] (table 1). AKT1 hydroxylation is mediated by PHD2, which in turn is the main regulator of HIF-1α hydroxylation [23,[50][51][52]. The interaction promotes AKT1 functional inhibition, while, similarly to what was observed for PKCδ, it seems to have no effect on AKT1 degradation.…”
Section: Von Hippel-lindau Protein and The Regulation Of Kinases Activitymentioning
confidence: 70%
“…S6E). PHD2 contains a highly conserved myeloid nervy deformed epidermal autoregulatory factor 1 homolog (MYND)–type zinc finger ( 28 , 29 ) with two conserved CXXC (two cysteines separated by two other residues) domains C21/24 and C33/36; the two mutations that affect PHD2 activity fall within one or the other of these conserved domains. To determine whether the identified cysteine residues within PHD2 were important for association with HIF-1a, we assessed the interaction of mutant or WT PHD2 with full-length glutathione S -transferase (GST)–HIF-1α.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to its C-terminal PHD domain, PHD2 also has an N-terminal, evolutionary-conserved, MYND-type zinc finger, a feature that is absent in both PHD1 and PHD3 ( 28 , 29 ). The zinc finger of PHD2 is essential for efficient hydroxylation of HIF-1α ( 11 , 28 , 29 ). Supporting the essentiality of the zinc finger, we found that H 2 S persulfidates PHD2 at five different cysteine residues, two of which are within the zinc finger motif.…”
Section: Discussionmentioning
confidence: 99%
“…2C). We have previously generated the corresponding control mouse line in which the coding sequence of murine Phd2 exon 1 is replaced by that of wild-type human PHD2 exon 1 (hereafter referred to as Phd2 WT ) (24). There was no difference in litter sizes between the two genotypes (5.19 ± 1.38 [SD] for Phd2 WT/WT × Phd2 WT/WT crosses vs. 5.00 ± 1.93 [SD] for Phd2 Tib/Tib × Phd2 Tib/Tib crosses; n = 16 litters for each; P = 0.75).…”
Section: Mutations In the Vicinity Of Asp-4 And Cys-127 Of Phd2 Impairmentioning
confidence: 99%